2015
DOI: 10.1186/s40608-016-0082-8
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-induced obesity triggers alveolar bone loss and spontaneous periodontal disease in growing mice

Abstract: BackgroundThe relationship between high-fat food consumption and obesity is well-established. However, it is as yet unclear whether high-fat diet (HFD)-induced obesity in childhood and adolescence determines age-related changes in jaw bone health. The aim of this study is to examine the age-related influence of HFD-induced obesity on mandibular bone architecture and the structure of the periodontium in growing mice.MethodsMale C57BL/6 J mice (6-weeks-old) were divided into two groups (n = 6 each): the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 39 publications
9
69
1
Order By: Relevance
“…This is related to the fact that most studies that evaluated etiopathogenic processes of periodontal diseases in rodents used different disease induction models, 31 which may be, in some cases, more extreme than the natural occurrence of periodontitis. Therefore, these experimental models have recently been criticized and investigated, especially by taking into consideration the possibility of observing periodontal breakdown without any “external” challenge 3 , 4 . The present results indicate that some CC lines showed a significant “spontaneous” bone loss in response to an HFD consumption despite the absence of classic periodontal disease induction such as ligatures, bacteria, etc.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is related to the fact that most studies that evaluated etiopathogenic processes of periodontal diseases in rodents used different disease induction models, 31 which may be, in some cases, more extreme than the natural occurrence of periodontitis. Therefore, these experimental models have recently been criticized and investigated, especially by taking into consideration the possibility of observing periodontal breakdown without any “external” challenge 3 , 4 . The present results indicate that some CC lines showed a significant “spontaneous” bone loss in response to an HFD consumption despite the absence of classic periodontal disease induction such as ligatures, bacteria, etc.…”
Section: Discussionmentioning
confidence: 79%
“…Periodontitis is considered to be one of the most common inflammatory diseases in humans, resulting in destruction of tooth‐supporting tissues and irreversible alveolar bone loss (ABL) and leading, in some cases, to tooth loss 1 . Today, it is evident that susceptibility to periodontitis is attributed to interplay of both host genetic background 2 and environmental factors, including lifestyle, obesity, and high‐fat diet (HFD) 3 , 4 . Type 2 diabetes mellitus (t2DM) is a complex metabolic disease that is characterized by hyperglycemia resulting from insulin resistance.…”
mentioning
confidence: 99%
“…The visits additionally provide a window of opportunity for potential behaviour change and lifestyle modification [19, 20]. A recent pilot study evaluating the feasibility of regular weighing in the context of routine antenatal care reported that weighing took on average 1–2 min of a midwife’s time, was simple to do, and did not significantly add to midwives existing workloads [21]. A qualitative analysis of pregnant women’s experience of routine weighing reported that weighing during antenatal appointments was an acceptable intervention that when introduced did not cause distress or anxiety [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, PI, which represents participants’ plaque control and quality of oral hygiene, showed no significant difference among the three study groups. Also, BMI, which is an objective index that is likely related to inflammation and periodontal status, 15 , 37 showed no significant difference among groups. Therefore, lack of significant differences in these confounding variables (PI and BMI) is a strength of the present study and enabled more precise evaluation of the effect of hypertriglyceridemia and gemfibrozil intake on periodontal parameters.…”
Section: Discussionmentioning
confidence: 86%
“…By creating reactive oxygen species in the process of neutrophil activity, ionic balance is disrupted and periodontal tissue is damaged by production of free oxygen radicals such as OH and H 2 O 2 , leading to development of periodontal disease 12 , 32 . Factors capable of eliminating these free radicals or inhibiting their production can prevent the development or progression of periodontal disease 33–37 . Gemfibrozil belongs to a group of drugs known as “fibrates.” Fibrates enhance oxidation of fatty acids in the liver and muscles and decrease the rate of hepatic lipogenesis; 9 also, they increase production of apoA‐I and apoA‐II in the liver, which may contribute to an increase in plasma level of HDL 38 .…”
Section: Discussionmentioning
confidence: 99%